Do street status and centrality matter for post-socialist memory policy? The experience of Ukrainian cities - Gnatiuk, Oleksiy. Autor; Glybovets, Victoria. Autor (IGiPZ PAN, 2020)
Naming and renaming of urban space often is sensitive in terms of the street location and status and implies categorization of streets according to the perceived importance of a street name. Thus, different locations in the city have different symbolic significance, and the urban toponymy could be read as a spatial projection of the societal axiological system. This article represents an attempt to study the importance of location (centrality vs. peripherality) and status (significance) of the urban public spaces in the 36 largest Ukrainian cities in terms of symbolical value and memory policy. The findings indicate that both investigated factors constitute an important tool of identity shaping and historical memory policy, but their influence and manifestation may vary considerably depending on specific historical, cultural and (geo)political conditions. Therefore, although the central parts of cities and the main urban arteries have tangibly larger symbolic significance, the toponymy of less presentable urban areas may be no less eloquent in the critical toponymy studies.
24 cm
Keywords: toponimia miejska; zmiany nazw ulic; tożsamość; polityka upamiętniania; położenie ulicy; status ulicy; Ukraina